1999
DOI: 10.1890/1051-0761(1999)009[0135:iossth]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Spatial Scale to Habitat Use by Breeding Birds in Riparian Forests: A Hierarchical Analysis

Abstract: Patterns of habitat use by breeding birds were studied in cottonwood riparian forests along 100 km of the South Fork of the Snake River in southeastern Idaho, United States, from 1991 to 1994. A hierarchical approach was used to examine habitat use at three spatial scales: microhabitat (local vegetation characteristics), macrohabitat (cottonwood forest patch characteristics), and landscape (composition and patterning of surrounding [matrix] vegetation types and land uses). This paper addresses a series of pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
240
3
9

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(274 citation statements)
references
References 43 publications
22
240
3
9
Order By: Relevance
“…The reverse was also equally true, as local-level variables added significantly to the same number of models when we accounted for parks and surrounding forest cover. Other studies have demonstrated support for landscape-level effects on birds in urban areas and generally have concluded that urbanization around forest patches and riparian areas affects bird diversity and abundance within these areas (e.g., Munyenyembe et al 1989, Smith and Schaefer 1992, Bolger et al 1997, Germaine et al 1998, Saab 1999. However, results from multiple-scale studies have not consistently shown that these effects are significant (Berry andBock 1998, Clergeau et al 1998).…”
Section: Local Vs Landscape Habitat Predictorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reverse was also equally true, as local-level variables added significantly to the same number of models when we accounted for parks and surrounding forest cover. Other studies have demonstrated support for landscape-level effects on birds in urban areas and generally have concluded that urbanization around forest patches and riparian areas affects bird diversity and abundance within these areas (e.g., Munyenyembe et al 1989, Smith and Schaefer 1992, Bolger et al 1997, Germaine et al 1998, Saab 1999. However, results from multiple-scale studies have not consistently shown that these effects are significant (Berry andBock 1998, Clergeau et al 1998).…”
Section: Local Vs Landscape Habitat Predictorsmentioning
confidence: 99%
“…Thirdly, the distribution of birds in urban areas has been investigated using spatial-structuring theories of ecological communities in which local-scale habitat features are viewed in relation to the surrounding landscape features (e.g., Bolger et al 1997, Rottenborn 1999, Saab 1999, Odell and Knight 2001. Spatialstructuring studies have often indicated that the surrounding landscape characteristics (100 ha to <30,000 ha) provide significant additional information to local-scale bird habitat models that include only local, site-level (<3 ha) habitat characteristics (Smith and Schaefer 1992, Blair 1996, Bolger et al 1997, Germain et al 1998, Rottenborn 1999, Mörtberg 2001.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with birds have been rather equivocal. Several have found patch-level variables more important determining factors of species occupancy or abundance (e.g., Berry and Bock 1998, Estades 1999, Mortberg and Wallentinus 2000, Bajema and Lima 2001 while other studies have found landscape variables to be the primary explanatory factors (e.g., Jansson and Agelstam 1999, Saab 1999, Howell et al 2000, Loyn et al 2001). In addition, there are interspecific factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is presumably not a single 'best' spatial scale at which to associate species and their habitats for all species or ecological conditions, it is possible to reveal relevant ecological associations when the scale of analysis approaches the operational scale of the process of interest. Studies often use expert knowledge to set the scale of analysis, or in some cases use expert-informed designs to collect data at 'fine-' versus 'large-' spatial scales to compare their relative explanatory power (e.g., Saab 1999;Coppeto et al 2006;Cunningham et al 2014). Unfortunately, information regarding the ecological processes shaping the distribution or abundance of a species is often lacking, let alone the spatial scale at which these processes may act.…”
Section: Introductionmentioning
confidence: 99%